COVID-19: Cardiovascular perspective - Acharya, Kiran Prasad; Poudel, Pratima; Sherpa, Kunjang; Adhikari, Chandra Mani (Nepalese Heart Journal, 2020)
Introduction: Recently the outbreak of COVID-19 has created a nuisance in the health care system throughout the world. There are multiple early reports covering the cardiovascular perspective of COVID-19. However, there are limited guidelines/protocols addressing the issue. With the emerging pandemic, data is ever-changing and so is our understanding of the cardiovascular implication of COVID-19.